The Effect of Traditional Games in Overcoming School Bullying among Madrasah Ibtidaiyah Students - Ashar Ashar; Abdul Wahid; Syarifah Nur Fajrin; Wahyullah Alannasir; Maria Teresa M. Fajardo (Universitas Islam Negeri (UIN) Salatiga, 2025)
Background & objectives: Bullying in schools remains a significant concern, manifesting in various forms, including physical aggression, verbal abuse, and social exclusion. This study investigates the effectiveness of traditional games in reducing bullying behavior among students at MIN 1 Makassar. Method: Using a quasi-experimental One-Group Pretest-Posttest Design, 60 students were selected through purposive sampling. Data were collected using a questionnaire and analyzed using paired sample t-tests to determine statistical significance. Results: The findings of this study are: 1) bullying practices before the traditional game intervention were in three categories, namely very often 64%, frequent category 17%, never reaching 20%; 2) bullying practices after the traditional game intervention were in three categories, namely very often 24%, frequent category 9%, never reaching 67%; 3) the results of the statistical test obtained t = 15.03, p = 0.032, thus proving that traditional games have a significant influence on bullying behavior. Contribution of theory: Theoretically, the results of this study have developed a theory of Islamic education for the instillation of the values of tasamuh, ta'awun, and ihtiram that support character education. The integration of traditional games in school activities not only enhances social skills but also reinforces moral and ethical behavior. This study highlights the importance of incorporating culturally relevant educational tools to address bullying and promote a harmonious school environment. Limitations & Recommendations: Future research should explore long-term impacts and scalability in different educational settings to validate these findings further.